2024
DOI: 10.1021/acsnano.3c11129
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Ceramization of Nanoscale Interface Enables Aerogel with Thermal Protection at 1950 °C

Quan Yuan,
Liwei Yan,
Jinfeng Tian
et al.

Abstract: Conventional carbon fiber felt-reinforced aerogel composites are often used as lightweight thermal protection systems (TPSs) for aerospace craft. However, due to their poor oxidation resistance, they have gradually failed to handle increasingly harsh thermal environments. In this work, a nanoscale composite coating interface of SiC-ZrC ceramic precursor is first constructed on the fiber surface. Subsequently, using the coated fiber felt as a three-dimensional skeleton and through polymerization-induced phase s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…As an advanced thermal protection material, aerogel's thermal insulation and ablative resistance performances are of vital importance [23][24][25][26]. Specifically, thermal stability is a significant factor for ablative resistance [27][28][29][30][31].…”
Section: Thermal Stability Mechanical Property and Thermal Insulation...mentioning
confidence: 99%
“…As an advanced thermal protection material, aerogel's thermal insulation and ablative resistance performances are of vital importance [23][24][25][26]. Specifically, thermal stability is a significant factor for ablative resistance [27][28][29][30][31].…”
Section: Thermal Stability Mechanical Property and Thermal Insulation...mentioning
confidence: 99%
“…Hou et al [3] demonstrated that anticorrosive coatings constitute the largest proportion (66.15%) of direct corrosion costs. Currently, the anticorrosive coatings in use include (1) graphene coatings [4][5][6] are primarily used on metal substrates in marine environments or those exposed to high concentrations of chloride ions [7,8]; (2) epoxy coatings [9][10][11] are mainly applied to metal substrates in industrial warehouses with lower protection needs [12]; (3) polyurethane coatings [13][14][15], due to their excellent stress-strain properties, are preferred for metal substrates in scratchprone environments [16,17]; (4) ceramic coatings [18][19][20], known for their high-temperature resistance, are primarily used on aerospace component surfaces [21,22]; and (5) superamphiphobic coatings [23,24], which act as active protective layers on substrates and can function in a variety of complex environments [25][26][27].…”
Section: Introductionmentioning
confidence: 99%